1990
DOI: 10.1002/jhrc.1240131009
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residue analysis in food with CGC — study of long‐term stability by the use of different injection techniques

Abstract: SummaryAn experiment was designed to study the long-term stability of analyses of pesticide residues in a complex food matrix using three different injection techniques. A spinach sample was spiked with five sulfur-containing pesticides of varying volatility and thermolability: arinphos-ethyl, dimethoate, methiocarb, ethiofencarb, and tri-allate. Tri-allate was selected as internal standard because of its thermal stability and its good chromatographic properties. Flame photometric detection resulted in chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Nevertheless, repeated injections of "dirty" samples result in quick deterioration of injector performance [3] due to contamination of the front part of column with non-volatile deposits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, repeated injections of "dirty" samples result in quick deterioration of injector performance [3] due to contamination of the front part of column with non-volatile deposits.…”
Section: Introductionmentioning
confidence: 99%
“…With on-column injection, more accurate results for troublesome compounds may be expected compared to splitless injection as long as a clean GC system is used. Nevertheless, repeated injections of "dirty" samples result in quick deterioration of injector performance [3] due to contamination of the front part of column with non-volatile deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, thermal degradation is minimized, because the residence time of the components at elevated temperatures is reduced compared with conventional split and sp!itless injection. The quantitative performance of FIN injection systems appears to be comparable to that of on-column injection while at the same time column contamination due to the presence of residue components in the sample, which is frequently observed in on-column sample introduction, is absent [35]. Despite the good results obtained by Vogt using the PTV injector in early large volume sampling experiments, there was hardly any interest in the PTV injector for large volume sampling in the decade following that publication.…”
Section: Programmed Temperature Vaporizing Injectionmentioning
confidence: 99%
“…On-column and PTV injection represent other sample introduction alternatives which may be assumed to reduce and/or eliminate matrix effects. Direct injection of sample onto the analytical column in the former and slow evaporation of sample in the latter technique are the inherent features offering potential for elimination of discrimination, degradation, and other negative effects [21][22][23]. In spite of these assumptions, Mol et al have reported matrix effects occurring in some extent during analyses of nitrogen and phosphorus containing pesticides by PTV-GC [24].…”
Section: Introductionmentioning
confidence: 99%